Lewis Antigen Phenotype and Survival of Patients With Pancreatic Cancer. Issue 10 (November 2020) - Kwon, Sohee; Kim, Sungsoo; Giovannucci, Edward L.; Hidalgo, Manuel; Markey, Mia K.; Bovik, Alan C.; Kwon, Man Jae; Kim, Kwang Joon; Im, Hyungsoon; Park, Jeong Youp; Bang, Seungmin; Park, Seung Woo; et al.
Abstract : Objectives: The association of Lewis antigen phenotype with survival of patients with pancreatic ductal adenocarcinoma was investigated. Methods: A total of 1187 patients diagnosed with pancreatic ductal adenocarcinoma were evaluated in a prospective cohort. Patients were classified into 3 different groups according to Lewis antigen phenotype: Lewis antigen (1) A positive [Le(a+b−)], (2) B positive [Le(a−b+)], and (3) negative [Le(a−b−)]. Risk of mortality was analyzed with Cox regression after adjusting for other predictors. Results: The risk of mortality increased in the order of Le(a+b−), Le(a−b+), and Le(a−b−) [reference; hazard ratio (HR), 1.27; 95% confidence interval (CI)], 1.03–1.57; P = 0.02; and HR, 1.65; 95% CI, 1.31–2.09; P < 0.001] after adjusting for other predictors. Among patients with serum carbohydrate antigen (CA) 19-9 lower than 37 U/mL, the association seemed more apparent (reference; HR, 1.50; 95% CI, 0.77–2.29; P = 0.22; and HR, 2.10; 95% CI, 1.10–4.02; P < 0.02). Conclusions: The risk of mortality increased in the order of Le(a+b−), Le(a−b+), and Le(a−b−). The difference in prognosis according to the Lewis antigen phenotype was more pronounced in the low CA 19-9 group, which suggests that the Lewis antigen phenotype works as a biomarker predicting the prognosis of patients with pancreatic cancer with undetectable CA 19-9 level. Abstract : Supplemental digital content is available in the text.